Does Saccharomyces cerevisiae Require Specific Post-Translational Silencing against Leaky Translation of Hac1up? - Ali Tehfe; Talia Roseshter; Yulong Wei; Xuhua Xia (Microorganisms, 2021)
HAC1 encodes a key transcription factor that transmits the unfolded protein response (UPR) from the endoplasmic reticulum (ER) to the nucleus and regulates downstream UPR genes in Saccharomyces cerevisiae. In response to the accumulation of unfolded proteins in the ER, Ire1p oligomers splice HAC1 pre-mRNA (HAC1u) via a non-conventional process and allow the spliced HAC1 (HAC1i) to be translated efficiently. However, leaky splicing and translation of HAC1u may occur in non-UPR cells to induce undesirable UPR. To control accidental UPR activation, multiple fail-safe mechanisms have been proposed to prevent leaky HAC1 splicing and translation and to facilitate rapid degradation of translated Hac1up and Hac1ip. Among proposed regulatory mechanisms is a degron sequence encoded at the 5′ end of the HAC1 intron that silences Hac1up expression. To investigate the necessity of an intron-encoded degron sequence that specifically targets Hac1up for degradation, we employed publicly available transcriptomic data to quantify leaky HAC1 splicing and translation in UPR-induced and non-UPR cells. As expected, we found that HAC1u is only efficiently spliced into HAC1i and efficiently translated into Hac1ip in UPR-induced cells. However, our analysis of ribosome profiling data confirmed frequent occurrence of leaky translation of HAC1u regardless of UPR induction, demonstrating the inability of translation fail-safe to completely inhibit Hac1up production. Additionally, among 32 yeast HAC1 surveyed, the degron sequence is highly conserved by Saccharomyces yeast but is poorly conserved by all other yeast species. Nevertheless, the degron sequence is the most conserved HAC1 intron segment in yeasts. These results suggest that the degron sequence may indeed play an important role in mitigating the accumulation of Hac1up to prevent accidental UPR activation in the Saccharomyces yeast.